THE EFFECT OF ONLINE GAME ACTIVITIES ON STUDENT LEARNING MOTIVATION - E Eliyani; Novi Fitriandika Sari (Jurnal Pelita Pendidikan, 2021)
The activity of playing an online game in a person will affect the value of student learning motivation. This study was aimed to know the effect of student activity on the online game to student learning activity in class X SMAN 1 Silangkitang. The research was used a quantitative method with the sample were 140 students by a total sampling technique. The instrument of this research used an online game activity and a student learning questioner. The data analysis technique used a simple correlation. The result showed that the online game frequency was 74.5%, the time of playing an online game was 68.2%, playing a popular game online was 72.9%, and playing a game online 48%. The total resulted in R = 0.349 with the total t-total > t-table was 4.373 > 0.159 with a total significant 5%, which means that there was an effect on student learning motivation.